Effect of long-term fertilization on zinc distribution and its uptake by wheat (Triticum aestivum) - DAS, ANIT; MEENA, MAHESH C; DWIVEDI, B S; DATTA, S P; DEY, ABIR (The Indian Journal of Agricultural Sciences, 2021)
Zinc (Zn) is one of the seventeen essential nutrients required for proper growth and development of plants. Majority of soils of India (about 43% of its cultivated soil) are deficient in Zn. Long-term fertilizer experiments (LTFE) are the perfect platform to investigate the impact of integrated nutrient management (INM) over a long period of time on Zn availability and uptake by crops. With this aim, soil samples were collected from an on-going 47 year-old longterm fertilizer experiment at ICAR-Indian Agricultural Research Institute (ICAR-IARI), New Delhi after harvesting of wheat during April, 2018. The selected fertilizer and manurial treatments includes control, N alone, NP, NPK, 150% NPK, NPK+Zn and NPK+FYM were studied. Results of the study reveal that yield of wheat, Zn content and uptake varied from 1.95-5.58 t/ha, 29.8-42.3 mg/kg, and 96.5-368 g/ha, respectively, across the nutrient management practices. It was also found that residual Zn was the major fraction in soil which accounted for 86-90% of the total Zn followed by oxide bound Zn (5.4-9.2%), organically bound Zn (1.9-3.8%), carbonate bound Zn (0.34-0.82%) and water soluble plus exchangeable Zn (0.26-0.58%). Grain yield of wheat was at par in NPK+Zn and NPK+FYM indicating that similar response of the applied Zn as compared to integrated nutrient management. Thus, NPK+Zn are the best option for producing Zn-fortified grains and sustainable crop production.